PREDATOR ANAK : HUKUMAN CAMBUK DALAM QANUN ACEH - Hidayat; M. Iqbal Irham (LPPM STAI DARUSSALAM LAMPUNG, 2022)
This study aims to contribute in handling cases of violence against children that are worrying in terms of the application of the caning punishment contained in the Aceh Qanun and this case continues to increase every year and is designated as an extraordinary crime. data and the law as the main source From the analysis obtained, it turns out that punishment for perpetrators of sexual violence against children does not have a significant effect, then the Aceh Qanun has the capacity to provide effective punishment coupled with other punishments with the Ta'zir concept. It is hoped that the Aceh Qanun will become the main reference in the formation of laws, even though the hierarchical status is only in Regional Regulations that are adapted to the conditions of the times that do not violate the established procedures.